Study of the influence of gust fronts and topographical features in the development of severe thunderstorms across South Africa - Mofokeng, Puseletso Samuel (University of the Witwatersrand, Johannesburg, 2024)
South Africa experiences a variety of severe thunderstorms which occasionally leads to a large quantity of small-sized or large-sized hailstones, heavy rain and flash flooding, strong damaging straight-line winds, and/or even tornadoes. For the base period, June 2016 to June 2021, a significant percentage of these severe storms was triggered by topographic features. The Unified Model (UM) at 4 km horizontal grid resolution was used and found to be unable to predict topography-generated vertical wind shear and the associated severe thunderstorms. This inability of the model necessitated the development of a conceptual model by relating the rapid cooling of the cloud-top temperatures with high resolution topographic maps. This means, satellite images were used to deduce the connection of atmospheric fluids (gust fronts) with near linear, concave and/or downslope topographical features. Severe thunderstorms included those connected to the large amounts of vorticity advection (e.g. 500 hPa level), development of low-level mesoscale circulations within the synoptic settings and the resultant vertical wind shear in the lower tropospheric levels. Large amounts of negative vorticity advection are typical with strong horizontal shear and curvature; they are often correlated with trough axes that lean from the south-west to north-east. The usage of large amounts of negative vorticity advection transcends to whether discrete severe thunderstorms will be characterised by heavy rain and flash-flooding or hail with damaging winds. Moreover, the interaction of topography with gust fronts of the upwind thunderstorms linked with large amounts of negative vorticity advection is also investigated. The impacts of storms studied in this dissertation posed a major threat to property, livelihood, agriculture, human and animal lives or even immediate to residual economic loss. This research is aimed at improving the service level for the benefit of disaster management agencies and the public at large. An in-depth study of microscale events such as tornadoes and landspouts was also conducted to improve lead-time for their nowcasting.
A research report Submitted in partial fulfillment of Master of Science degree in Meteorology to the Faculty of Science, School of School of Geography, Archaeology and Environment, University of the Witwatersrand, Johannesburg 2024
Keywords: Cut-off low pressure; Cloud-top temperatures; Severe thunderstorms; Flood; Gust front; Mid-tropospheric (MTS) circulation; Sever storm; Storm deflection; Tornado; Tornadogenesis; Vorticity; SDG-15: Life on land